EKSPROPRIASI MELALUI UTANG DALAM STRUKTUR KEPEMILIKAN ULTIMAT - Siregar, M.B.A., Ak., Dr. Baldric (Journal of Indonesian Economy and Business, 2008)
This study addresses ultimate ownership issue and investigates its implications on leverage. By using sample consists of firms listed in the Jakarta Stock Exchange for the period from 2000 to 2004, this study shows that the publicly traded firm ultimate ownership is concentrated in the hands of controlling shareholders. Ownership concentration can be divided into those of cash flow rights and control rights. Those two concentrations do not go together but have different implications. The controlling shareholders enhance their control domination through pyramid structures and crossholdings among firms. Control flow rights consequently exceed cash flow rights. The cash flow right concentration is a financial incentive to avoid expropriation. This conclusion is support by evidence of negative effects of cash flow rights on leverage. On the other hand, control right concentration is an incentive to generate private benefits through expropriation. This conclusion is support by evidence of positive effects of control rights on leverage. When control and cash flow rights are separated, the controlling shareholders have higher incentive to expropriation by participating in management. This is so because of higher negative effect of cash flow right leverage on leverage.Keywords: cash flow rights, control rights, cash flow right leverage, pyramiding, cross-holding,